2016
DOI: 10.1017/s0950268816001126
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial resistance ofSalmonellaserovars isolated from poultry in Ghana

Abstract: Poultry are possible sources of non-typhoidal Salmonella serovars which may cause foodborne human disease. We conducted a cross-sectional study to determine the prevalence of Salmonella serovars in egg-laying hens and broilers at the farm level and their susceptibility to antimicrobials commonly used in the poultry industry in Ghana. Sampling of faeces by a sock method (n = 75), dust (n = 75), feed (n = 10) and drinking water (n = 10) was performed at 75 commercial egg-laying and broiler farms in two regions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 38 publications
8
64
5
Order By: Relevance
“…(Mahmoud, 2016) showed that 43 samples among the examined 348 chicken samples (12.4%) collected from Dakahlia and Damietta Governorates, Egypt were positive for Salmonella. (Andoh et al, 2016) who successfully isolated Salmonella from 94/200 (47%) of the examined samples. In addition, (El-Sharkawy et al, 2017) revealed that Salmonella was recovered from 41% of the examined samples collected from broilers farms located in Kafr El-Sheikh.…”
Section: Resultsmentioning
confidence: 99%
“…(Mahmoud, 2016) showed that 43 samples among the examined 348 chicken samples (12.4%) collected from Dakahlia and Damietta Governorates, Egypt were positive for Salmonella. (Andoh et al, 2016) who successfully isolated Salmonella from 94/200 (47%) of the examined samples. In addition, (El-Sharkawy et al, 2017) revealed that Salmonella was recovered from 41% of the examined samples collected from broilers farms located in Kafr El-Sheikh.…”
Section: Resultsmentioning
confidence: 99%
“…[18] and Andoh et al . [19], whereas limited drug resistance in S . Gallinarum was observed by Dey et al .…”
Section: Discussionmentioning
confidence: 99%
“…In Ghana, there are fewer reports on antibiotic resistance of foodborne pathogens. The few studies available have also concentrated much on foodborne pathogens isolated from animals and humans (Mills-Robertson et al 2002;Awua-Boateng 2007;Nsoah, 2015;Donkor et al 2012;Adzitey 2015a;Adzitey et al 2015;Andoh et al 2016). However, vegetables in Ghana, including cabbages and lettuces are important sources of resistant foodborne pathogens and should not be ignored.…”
Section: Introductionmentioning
confidence: 99%